2018
DOI: 10.1371/journal.pone.0207787
|View full text |Cite
|
Sign up to set email alerts
|

PPE17 (Rv1168c) protein of Mycobacterium tuberculosis detects individuals with latent TB infection

Abstract: Latent tuberculosis infection (LTBI) is a clinically distinct category of Mycobacterium tuberculosis (Mtb) infection that needs to be diagnosed at the initial stage. We have reported earlier that one of the Mtb proline-proline-glutamic acid (PPE) proteins, PPE17 (Rv1168c) is associated with stronger B-cell and T-cell responses and could be used to diagnose different clinical categories of active TB patients with higher specificity and sensitivity than PPD and ESAT-6. Based on these observations we further test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…PE35, an RD1-encoded antigen, can significantly discriminate pulmonary or extra-pulmonary TB patients with healthy BCG-vaccinated individuals ( Mukherjee et al, 2007 ). Another good example is PPE17, whose N-terminal induces high immunogenic response and had greater potential to be a sero-diagnostic marker than full-length PPE17 ( Abraham et al, 2017 ), which could screen the latently infected subjects ( Abraham et al, 2018 ). PPE2 may also serve as a serodiagnosis marker to detect the extra-pulmonary and smear-negative pulmonary cases ( Abraham et al, 2014 ).…”
Section: Future Applications Of Pe/ppe Family Proteins In Tb Vaccine mentioning
confidence: 99%
“…PE35, an RD1-encoded antigen, can significantly discriminate pulmonary or extra-pulmonary TB patients with healthy BCG-vaccinated individuals ( Mukherjee et al, 2007 ). Another good example is PPE17, whose N-terminal induces high immunogenic response and had greater potential to be a sero-diagnostic marker than full-length PPE17 ( Abraham et al, 2017 ), which could screen the latently infected subjects ( Abraham et al, 2018 ). PPE2 may also serve as a serodiagnosis marker to detect the extra-pulmonary and smear-negative pulmonary cases ( Abraham et al, 2014 ).…”
Section: Future Applications Of Pe/ppe Family Proteins In Tb Vaccine mentioning
confidence: 99%
“…Searching for novel immunodominant antigens of M.tb that play critical roles in regulating protective immune response is urgently required. PE/PPE proteins located in RD regions are considered to be the most promising candidates for TB vaccine development and diagnostic agents, especially secreted antigens (Abraham et al, 2018). Rv3425 (PPE57), which locates in the RD11 region and induces macrophage activation by augmenting the expression of MHC-II and pro-inflammatory cytokines (TNF-α, IL-6, and IL-12p40), has been confirmed with the potential to distinguish patients with active TB via QFT assay (Wang et al, 2013; Losi et al, 2016) and for use as an antigen for therapeutic or protective vaccine design (Xu et al, 2014; Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical samples, Rv1768-specific IgG and IgM levels in active TB patients are higher than in Healthy controls, and the ROC curve area AUC of Rv1768-specific antibodies are better than CE. However, the diagnostic sensitivity of Rv1768-specific IgG (82.22%) is less than PPE17 (about 95%) (Abraham et al, 2018). Detection of PPE17-specific IgG also discriminates individuals with latent TB from the QFT-negative subjects and exhibits a higher sensitivity (about 87%), as compared to currently used TB diagnostic antigens like ESAT6, CFP10, and PPD (Abraham et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopez-Ramos et al (2018) showed that the antibodies against MTB antigen P12037 has a sensitivity and specificity of 92% and 91%, respectively in diagnosing active TB when used in concert with sCD14. Other researchers have found that antibody to MTB antigens such as proline-prolineglutamic acid protein 17 (PPE17) (Abraham et al, 2018) and mycobacterial DNA binding protein (MDP-1) (Maekura et al, 2019) can differentiate between patients with LTBI and active TB. Maekura et al (2019) further showed that MDBP-1 may also be a good monitoring tool as persistently elevated IgG against MDBP-1 post anti-TB therapy could be associated with relapse after completion of treatment.…”
Section: Prospects With Detection Of Host Immune Biomarkers In Mtb Inmentioning
confidence: 99%